1999
DOI: 10.1161/01.hyp.33.4.1043
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Carbonic Anhydrase Accounts for the Direct Vascular Effects of Hydrochlorothiazide

Abstract: Abstract-Hydrochlorothiazide has been shown to exert direct vasodilator effects by activation of calcium-activated potassium (K Ca ) channels in human and guinea pig isolated resistance arteries. Since hydrochlorothiazide binds to and inhibits the enzyme carbonic anhydrase and because K Ca channel activation is pH sensitive, we investigated the role of intracellular and extracellular carbonic anhydrase in the vascular effects of thiazide diuretics. Small arteries were isolated from guinea pig mesentery and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 37 publications
2
89
1
3
Order By: Relevance
“…It was therefore suggested that the vasorelaxant effects of hydrochlorothiazide were due to inhibition of carbonic anhydrase and an effect of increased pH i on opening of K Ca . However, while this proposal is consistent with the known vasodilator effect of carbonic anhydrase inhibitors, 91,92 and may explain the acute vasodilator effects of thiazides in vivo at high doses, 90 there are two problems with this as an explanation of the mechanism of the action of thiazides as antihypertensive agents. First, the concentrations of thiazides needed to cause vasorelaxation in all these studies are considerably higher than those achieved therapeutically.…”
Section: Direct Actions On Blood Vesselssupporting
confidence: 68%
See 1 more Smart Citation
“…It was therefore suggested that the vasorelaxant effects of hydrochlorothiazide were due to inhibition of carbonic anhydrase and an effect of increased pH i on opening of K Ca . However, while this proposal is consistent with the known vasodilator effect of carbonic anhydrase inhibitors, 91,92 and may explain the acute vasodilator effects of thiazides in vivo at high doses, 90 there are two problems with this as an explanation of the mechanism of the action of thiazides as antihypertensive agents. First, the concentrations of thiazides needed to cause vasorelaxation in all these studies are considerably higher than those achieved therapeutically.…”
Section: Direct Actions On Blood Vesselssupporting
confidence: 68%
“…The authors' proposal that thiazides act via K + channels is consistent with an earlier report of increased (86Rb) efflux from ex vivo tail artery The ability of hydrochlorothiazide to reduce intracellular Ca 2+ and tone in noradrenaline-contracted guinea-pig mesenteric arteries was also attributed to K Ca opening. [87][88][89] Further studies 90 showed that the relaxant effects of hydrochlorothiazide were not shared by bendroflumethiazide, but that inhibitors of carbonic anhydrase also relaxed guinea-pig mesenteric arteries via opening K Ca and both hydrochlorothiazide and acetazolamide increased intracellular pH (pH i ). It was therefore suggested that the vasorelaxant effects of hydrochlorothiazide were due to inhibition of carbonic anhydrase and an effect of increased pH i on opening of K Ca .…”
Section: Direct Actions On Blood Vesselsmentioning
confidence: 99%
“…Although it has been suggested that thiazide-induced vasodilation is mediated by the opening of Ca 2+ -activated K + channels or by Losartan-hydrochlorothiazide therapy Y Yamada et al inhibition of carbonic anhydrase, 34,35 the precise mechanisms by which thiazide-like diuretics inhibit vasoconstriction and vascular growth are still unclear. The predominant activity of thiazide diuretics is to inhibit a directly coupled Na + -Cl -co-transporter along the distal convoluted tubule of the kidney, and this transporter is not expressed by vascular smooth muscle or cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin may be required for the thiazide-induced increase in AQP2. In the aspect of pharmacologic properties, HCTZ significantly inhibits carbonic anhydrase activity, whereas bendroflumethiazide lacks the carbonic anhydrase inhibiting activity (35).…”
Section: Hctz Treatment Partially Reverses Li-induced Aqp2 Downregulamentioning
confidence: 99%